A RF front-end for DVB-SH based on current conveyors. Issue 7 (July 2015) - García-Vázquez, H.; Khemchandani, S.L.; del Pino, J.
Abstract Inductors are used extensively in Radio Frequency Integrated Circuits to design matching networks, load circuits of voltage controlled oscillators, filters, mixers and many other RF circuits. However, on-chip inductors are large and cannot be ported easily from one process to the next. Due to modern CMOS scaling, inductorless RF design is rapidly becoming possible. In this paper a new methodology for designing the RF frontend necessary for the DVB-SH in a 90 nm CMOS technology based on the use current conveyors (CC) is presented. The RF frontend scheme is composed of a second generation CC (CCII) LNA with asymmetric input and output, an asymmetric to differential converter, and a passive differential mixer followed by two CCII transimpedance amplifiers to obtain a high gain conversion. Measurements show a conversion gain of 20.8 dB, a 14.5 dB noise figure, an input return loss (S11) of −14.3 dB and an output compression point of −3.9 dBm. This combination draws 28.4 mW from a ±1.2 V supply.